Isokinetic rotator cuff functional ratios and the development of shoulder injury in collegiate baseball pitchers - Vogelpohl, R. E.; Kollock, R. O. (International Journal of Athletic Therapy & Training, 2015)
Context: Shoulder injury in baseball pitchers is a very common problem and has been linked to an imbalance in rotator cuff strength. Recently, the use of functional shoulder strength ratios has become more popular because they more closely resemble the actions of the shoulder during the throwing motion.